Fungsi Bahasa dalam Cerpen Berjuta Rasanya Karya Tere Liye: Perspektif Roman Jakobson - Luthfialana, Mawaddata; Hasyim, Muhammad; Al Anshory, Abdul Muntaqim (ppjbsip, 2024)
The presence of language makes it easier for humans to interact as a means of communication. In its function, literary language can support the creative abilities of writers, and even become a language with artistic value. The aim of this research is to understand and describe the function of language contained in the short story